ANALISIS KERAWANAN LONGSOR DI KECAMATAN NGRAYUN KABUPATEN PONOROGO - Vania Mugareta, Atmaja; Anggoro Sigit, Agus; Priyana, Yuli; Taryono, Taryono (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2026)
Ngrayun Subdistrict, Ponorogo Regency is an area with a high level of landslide vulnerability due to hilly topography, high rainfall, and uncontrolled land use changes. This study aims to map landslide vulnerability levels, identify dominant factors causing landslides, and formulate disaster mitigation strategies in Ngrayun Subdistrict. The method used is spatial analysis based on Geographic Information System (GIS) with overlay techniques on four parameters: rainfall, slope gradient, soil type, and land use, which have been scored based on vulnerability levels. Primary data were obtained through field observations, while secondary data were sourced from relevant agencies and scientific literature. The results show that landslide vulnerability levels in Ngrayun Subdistrict are divided into three classes: less vulnerable (7,997.49 ha), vulnerable (9,200.47 ha), and highly vulnerable (38.41 ha), with the vulnerable class dominating the research area. The dominant factor causing landslides is high rainfall (>2,500 mm/year) with a percentage of 30.77%. Recommended mitigation strategies include structural mitigation such as protective infrastructure development, reforestation, and installation of landslide detection devices, as well as non-structural mitigation including disaster preparedness training and provision of temporary shelters in landslide-prone areas.